Differential Pulse Voltammetry Determination of Anti-Hypertensive Drug Hydrochlorothiazide in Pharmaceuticals Using Glassy-Carbon Electrode Modified by Electropolymerization with L- and D- Glutamic Acids - Salazar-Gonzalez, R; Gonzalez-Vargas, C; Gonzalez-Vargas, C (Electrochemical Science Group, 2018)
A simple and sensitive electrochemical sensor based on glassy carbon electrode modified by electropolymerization with both poly-glutamic acid enantiomers L- and D (GC-PGA) was developed to detect the anti-hypertensive drug hydrochlorotiazide (6-chloro-3,4-di-hydro-2H-1, 2,4-benzo-thiadiazine-7-sulfonamide-1,1 dioxide, HCTZ) in pharmaceuticals samples. Raman spectroscopy and electrochemical impedance spectroscopy were carried out to characterize L-PGA and D-PGA film. These procedures confirm the production of a polymer through an amide bond and the formation of a film resistant to charge transference in both cases. Also, an increase in the oxidation peak current for HCTZ in Buffer Britton Robinson solution 0,1 M pH 2 was obtained using the modified electrodes. With GC/D-PGA and GC/L-PGA, the peak current increased 2 times compared to unmodified GC, when using differential pulse voltammetry. A novel electroanalytical method for the determination of HCTZ was developed with both modified electrodes, showing a less limit of determination: 0.03186 and 0.01829 mM to GC/L-PGA and GC/D-PGA, respectively, and a less limit of quantification with respect to the GC electrode. The methodology developed was applied in the determination of HCTZ from pharmaceutical forms. © 2018 The Authors.
Keywords: Glutamic Acid; Hydrochlorotiazide; electropolymerization; differential pulse voltammetry; glassy carbon electrode.